2020
DOI: 10.1101/2020.01.01.888354
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ATR expands embryonic stem cell fate potential in response to replication stress

Abstract: Unrepaired DNA damage during embryonic development can be potentially inherited by a large population of cells. However, the quality control mechanisms that minimize the contribution of damaged cells to developing embryos remain poorly understood.Here, we uncovered an ATR-and CHK1-mediated transcriptional response to replication stress (RS) in ESCs that induces genes expressed in totipotent two-cell (2C) stage embryos and 2C-like cells. This response is mediated by Dux, a multicopy retrogene defining the clea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 74 publications
0
23
2
Order By: Relevance
“…It is recently discovered that DNA damage is induced by the depletion of MERVL activator Zscan4 [ 3 , 31 ]. Responses of ATR and CHK1 to replication stresses activate Zscan4 and MERVL [ 20 ], implying that DNA damage-induced replication stress and Zscan4 reciprocally regulate each other. It will be interesting to investigate whether Nsd2 is involved DNA damage repair and its relationship with Zscan4 in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is recently discovered that DNA damage is induced by the depletion of MERVL activator Zscan4 [ 3 , 31 ]. Responses of ATR and CHK1 to replication stresses activate Zscan4 and MERVL [ 20 ], implying that DNA damage-induced replication stress and Zscan4 reciprocally regulate each other. It will be interesting to investigate whether Nsd2 is involved DNA damage repair and its relationship with Zscan4 in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated from cells by RNAiso Reagent (B9109, Takara) in DEPC water (B501005, Sangon Biotech) following by DNase I treatment in RNase-free tubes (401001, NEST Biotechnology). Reverse transcription was performed with 1 μ g purified RNA using Transcriptor First Strand cDNA Synthesis Kit (4897030001, Roche) as described previously [ 20 ]. qPCR analysis was carried out using SYBR Green qPCR Master Mix (H97410, Yeasen) and a qPCR detection system (CFX384 Real-Time System, Bio-Rad) according to standard protocols.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, recent research suggested that VE-821 showed a synergistic effect with PD-L1 inhibition in pancreatic cancer, and PD-L1 inhibition increased VE-821 sensitivity [40] . GRSF1 is necessary in the progression of ATR-dependent regulation on Dux, which is vital for the cleavage-speci c transcription [41] .Therefore, whether the combination with PD-L1 inhibition could improve antitumor function of VE-821 on HCC induced by GRSF1 is worth to be further discussed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, it has been reported that mouse embryos are particularly sensitive to the replication stress agent aphidicolin during ZGA 47 . Moreover, ATR, but not ATM, was recently shown to be required for the conversion of mouse embryonic stem cells into 2C-like cells, which are characterized by the activation of various ZGA markers 48 . Thus, hampering DDR through ATM but not ATR pathway could allow lowering the tolerance for DNA damage whilst ensuring genome stability during ZGA.…”
Section: Discussionmentioning
confidence: 99%